Book review: Ravi Chaudhry. Quest for Exceptional Leadership—Mirage to Reality (2E). Issue 1 (June 2019) - Kumar, Sushil
Ravi Chaudhry. Quest for Exceptional Leadership—Mirage to Reality (2E) . SAGE Publications.